Plasma regions, charged dust and field-aligned currents near Enceladus. (November 2015) - Engelhardt, I.A.D.; Wahlund, J.-E.; Andrews, D.J.; Eriksson, A.I.; Ye, S.; Kurth, W.S.; Gurnett, D.A.; Morooka, M.W.; Farrell, W.M.; Dougherty, M.K.
Abstract: We use data from several instruments on board Cassini to determine the characteristics of the plasma and dust regions around Saturn׳s moon Enceladus. For this we utilize the Langmuir probe and the electric antenna connected to the wideband receiver of the radio and plasma wave science (RPWS) instrument package as well as the magnetometer (MAG). We show that there are several distinct plasma and dust regions around Enceladus. Specifically they are the plume filled with neutral gas, plasma, and charged dust, with a distinct edge boundary region. Here we present observations of a new distinct plasma region, being a dust trail on the downstream side. This is seen both as a difference in ion and electron densities, indicating the presence of charged dust, and directly from the signals created on RPWS antennas by the dust impacts on the spacecraft. Furthermore, we show a very good scaling of these two independent dust density measurement methods over four orders of magnitude in dust density, thereby for the first time cross-validating them. To establish equilibrium with the surrounding plasma the dust becomes negatively charged by attracting free electrons. The dust distribution follows a simple power law and the smallest dust particles in the dust trail region are found to be 10 nm in size as well as in the edge region around the plume. Inside the plume the presence of even smaller particles of about 1 nm is inferred. From the magnetic field measurements we infer strong field-aligned currents at the geometrical edge of Enceladus. Abstract : Highlights: Different regions with specific plasma structure and B-field configurations. The dust is in equilibrium with the surrounding plasma (collective behavior). Minimum dust sizes: 1 nm (plume) and 10 nm (plume edge and dust trail). Overview of 20 flybys in dust and plasma densities, B-field and currents. We show strong field-aligned edge currents.